ANALISIS USAHA PENDEDERAN NILA (Oreochromis spp.) MODEL KEMITRAAN DI KECAMATAN KALASAN KABUPATEN SLEMAN - , DEPPY AMRISTA SANJOYO; , Suadi, S.Pi., M.Agr.Sc., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Partnership model in fish nursery is an attempt by a pattern of cooperation between the core company with fish farmer group as plasma through the agreement of both sides of the output and input prices. This study aims to determine the costs, revenues, and tilapia nursery business partnership model between PT Aquafarm Nusantara with Fish Farmers Group (FFG) Mina Jaya and Mina Soka Makmur. Thirty five respondents consisted of 23 respondents in FFG Mina Jaya and 12 respondents in Mina Soka Makmur. Among the selected members in Mina Jaya, 12 members join the partnership program and 11 of non-partner members. All respondents were selected using cluster random sampling method based on the size of pond. Data were analyzed using analysis of costs, revenues and earnings, as well as business analysis through the analysis of R/C ratio. At the same pond size of 1,000 m2, the study indicated the total cost of non-partner fish farmers were higher than fish farmer joining partnership program. The revenue and income analysis of pond size 1,000 m2, the non-partnership fish farmer earns more revenue and income than fish farmer joining partnership. However the t-test of R/C Ratio value indicated there no significant differences of R/C Ratio between the fish farmer joining partnership program and non-partners. The R/C Ratio was more than 1, indicating that the business is feasible to be continued.